PHILOSOPHY OF SPORT: MEANING, VALUES, AND THE HUMAN DIMENSION (International Conference on Economics, Finance, Banking and Management, 2025)
This article is dedicated to the philosophical interpretation of the phenomenon of sport. It examines key concepts in the philosophy of sport such as play, competition, corporeality, justice, virtue, and freedom. The role of sport in personality development, moral qualities, and societal progress is analyzed. Special attention is paid to the question of whether sport can serve not only physical development but also the spiritual improvement of the individual.